Comparative study on shear performance of blended pozzolonic RC beams with fly ash and recycled aggregates - Damera, Harikrishna; Murthy, N.R. Dakshina; Rao, N.V. Ramana (Journal of Structural Engineering, 2024)
Shear failure in a reinforced concrete beam is a sudden failure which is associated with crushing of concrete and is a brittle failure. A structural designer should be aware of various components of shear resisting mechanisms particularly the shear resistance of concrete. In this regard, an experimental investigation was carried out on forty simply supported reinforced concrete beams, to examine their shear performance of with and without shear reinforcement. This paper reports the results of a laboratory based experimental study aimed at studying shear performance of blended concrete beams with fly ash and recycled aggregates. Blended concrete beams of M35 and M45 grades were produced by partially replacing the cement by 25 percent fly ash and the Natural Coarse Aggregates (NCA) were replaced by Recycled Coarse Aggregates (RCA) in different fractions of 0,25,50,75 and 100 percentages. The experimental shear strength of blended concrete beams was then compared with predicted shear strength evaluated from various international codes and some existing empirical models in order to adjudicate the relevance of the experimental shear strength with the predicted shear strengths for beams without shear reinforcement.